RELIGIOSITY AND PERSONALITY IN PARTICIPANTS IN THE EIGHT-DAY--LONG ‘IGNATIAN’ RETREATS - WILCZEK, CEZARY (Studia Psychologica: Theoria et praxis, 2014)
The main purpose of this empiric research was to get an answer to the essential question: Do the personal religiousness and personality features change in the case of individuals subjected to the influence of the eight-day Ignatian retreats’ formation? The research group (N = 203) consisted of individuals in the age of 25-40 years who participated in the system of Ignatian retreats. The participants were divided into two groups: an experimental one comprised of long-term and advanced retreaters (N = 101) and a  control one of unadvanced retreaters (N = 102). The conducted empiric research verified the pre-formulated research hypotheses, indicating the appearance of essential changes regarding examined variables in the experimental group.